Coping experience of health concerns and physical disability for older Chinese people: A qualitative, descriptive study. (28th July 2017) - Mei, He; Turale, Sue
Abstract: In this qualitative, descriptive study, we explored the perspectives of older, community‐dwelling Chinese people regarding their experiences of coping with a physical disability and their health concerns. Twenty participants were interviewed in‐depth, and data were analyzed using content analysis. Five themes with 13 subthemes emerged that described older people's experiences of coping with health concerns and disability: (i) ignoring health concerns; (ii) managing self; (iii) seeking medical help; (iv) living with physical disability; and (v) relying on limited resources. Most participants did not have sufficient access to health services due to physical disability and financial deficits, so they tended to ignore their health conditions or tackle them independently before seeking medical help. At the same time, they were impacted on by social and cultural factors. Policies are required that offer more resources to community‐dwelling people with disabilities in China.